Demographic Perspective of Public Elementary Schools in the Province of Sorsogon - Janer, Susan S.; Deri, Ritzelda A. (Asia Pacific Higher Education Research Journal (APHERJ), 2020)
This study described the condition of public elementary schools (PES) in Sorsogon. It utilized descriptive research design through survey, interview, and documentary analysis. Findings revealed that Sorsogon City had the largest number of enrollees while Donsol and Castilla had the least. Sixty-eight percent (68%) of the PES enjoyed a 1:31 classroompupil ratio, while 32% had 1:32-1:64. Only 39% of PES had laboratory facilities. Meanwhile, a projected increase in enrolment of 15.6% by 2025 may result in more shortage of classrooms and laboratory facilities. At present, PES school heads are mostly middleaged males and new leaders. Their teachers are generally young females, new in the profession but pursuing advance education. This study recommends that improvement of physical facilities and laboratories in PES be prioritized. Moreover, the significant roles of school heads and teachers should also be considered in recommending solutions and actions to address problems confronting the PES in the province.